2014
DOI: 10.1016/j.it.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining class-I presentation and the DRiP hypothesis

Abstract: MHC class I molecules present peptides derived from intracellular proteins, enabling immune surveillance by CD8+ T cells and the elimination of virally infected and cancerous cells. It has been argued that the dominant source of MHC class I-presented peptides is through proteasomal degradation of newly synthesized defective proteins, termed defective ribosomal products (DRiPs). Here, we critically examine the DRiP hypothesis and discuss recent studies indicating that antigenic peptides are generated from the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 76 publications
2
63
1
Order By: Relevance
“…However, the cellular mechanisms and the identity of the proteins providing peptides for this rapid response pathway are still ill defined. Furthermore, the question of whether the pool of presented MHC peptides (the MHC peptidome or immunopeptidome) is mostly produced from normal, long-lived proteins, at the end of their functional lifetimes (3), or alternatively, from rapidly degraded immature proteins (4,5) is not yet settled (6)(7)(8). In cultured cells, upward to a third of the MHC peptidome was suggested to be derived from the latter.…”
Section: Dripome | Immunopeptidome | Dynamic Silacmentioning
confidence: 99%
“…However, the cellular mechanisms and the identity of the proteins providing peptides for this rapid response pathway are still ill defined. Furthermore, the question of whether the pool of presented MHC peptides (the MHC peptidome or immunopeptidome) is mostly produced from normal, long-lived proteins, at the end of their functional lifetimes (3), or alternatively, from rapidly degraded immature proteins (4,5) is not yet settled (6)(7)(8). In cultured cells, upward to a third of the MHC peptidome was suggested to be derived from the latter.…”
Section: Dripome | Immunopeptidome | Dynamic Silacmentioning
confidence: 99%
“…Classic biochemical studies have shown that MAP processing is initiated in the cytoplasm by proteasomal protein degradation followed by further trimming by cytosolic peptidases, transport in the ER, and final trimming by ER peptidases (8,(12)(13)(14)(15). According to the dominant paradigm, MAPs preferentially originate from defective ribosomal products (DRiPs) which can be created by several mechanisms such as nonsense-mediated decay (NMD), mRNA destabilization, or noncanonical translation in the cytosol or the nucleus (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the B lymphoblastic cell line 721.221, the source proteins were dominantly involved in declining prominence in metabolism, cell growth and/or maintenance, cell communication, and stress response (39), and in multiple sclerosis autopsy samples, they were dominantly involved in cellular assembly and organization, nervous system development and function, cellular growth, and proliferation (40). The similarities in source protein peptide sampling in MUTZ3 DCs and THP1MF, although unconfirmed, would imply similarities in protein turnover, because protein turnover correlates with source protein peptide sampling (43,44).…”
Section: Discussionmentioning
confidence: 99%